The Emergence and Prevalence of Informal Youth Self-published Fanzines in Lithuania - Kairaitytė-Užupė, Aušra; Ramanauskaitė, Egidija (Tautosakos darbai, 2023)
The article presents the phenomenon of informal newspapers fanzines published by the Lithuanian youth. Using a digitized collection of 500 fanzines from the 1990s and additional sources representing rock music, punk, science-fiction, and other subcultures, employing certain methods of textual analysis and ethnographic research (questionnaires, targeted interviews with zinesters, publishers, and collectors), the article analyses emergence of fanzines, their prevalence in Lithuania, and motivation for their publishing.The main results of the research show that the most active period of fanzine-publishing in Lithuania was 1990–2004 when a wave of subcultural self-expression among young people was spreading after the restoration of Lithuania’s independence. Fanzines as a phenomenon were characteristic not only of Lithuania’s major cities, but also of its regions. The main motivation to create fanzines signifies young people’s need to disseminate the issues of cultural life important to them yet absent from the official press, to express their creative potential, and to broaden their circle of the like-minded people.
Keywords: fanzines; informal publishing; youth; subculture